2016
DOI: 10.1097/adm.0000000000000247
|View full text |Cite
|
Sign up to set email alerts
|

The Availability of Ancillary Counseling in the Practices of Physicians Prescribing Buprenorphine

Abstract: Objectives We set out to examine physicians’ perceptions of the provision of ancillary services for opioid dependent patients receiving buprenorphine. Methods An email invitation describing the study was sent out by the American Society of Addiction Medicine to its membership (approximately 3,700 physicians) and other entities (for a total of approximately 7,000 email addresses). Email recipients were invited to participate in a research study funded by the National Institutes on Drug Abuse involving complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Prior studies of buprenorphine prescribers have found the majority of prescribers offered counseling within their practice settings and others refer patients to counseling in the community. 7,8 Furthermore, in a small sample of buprenorphine prescribers in New York City, 62% of respondents considered PIs to be of at least high importance for patients. 9 In addition, patients value psychosocial interventions, including brief counseling delivered by the prescriber, though some also believe PIs should not be a mandatory requirement of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies of buprenorphine prescribers have found the majority of prescribers offered counseling within their practice settings and others refer patients to counseling in the community. 7,8 Furthermore, in a small sample of buprenorphine prescribers in New York City, 62% of respondents considered PIs to be of at least high importance for patients. 9 In addition, patients value psychosocial interventions, including brief counseling delivered by the prescriber, though some also believe PIs should not be a mandatory requirement of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…A major issue relating to gaps in treatment capacity are that a minority of providers who would be eligible for the waiver have completed the training, 4,5 amounting to a national median of 5.9 providers per 100,000 patients 6 . Those who have completed the training are more likely to be located in urban areas, places with higher opioid-related mortality, and/or have fewer Medicaid versus private pay patients 4,7–9 . Providers have cited complexity in initiating buprenorphine treatment (including receipt of the waiver), concern over increased regulatory burdens, stigma related to OUD, and other general infrastructure issues as barriers to providing buprenorphine treatment, 5,10–13 and several telementoring projects 14,15 and hub-and-spoke systems 16,17 have been developed to increase willingness to prescribe.…”
mentioning
confidence: 99%